The Dynamic Response of an Arch Dam During a Recorded Low-Intensity Earthquake - Jorge P. Gomes; José V. Lemos (Applied Sciences)
The dynamic behavior of a concrete arch dam, the Baixo Sabor dam, built in Portugal, is investigated. A numerical model was developed to represent the dam, foundation, and reservoir system. This model was calibrated and validated through comparison with experimental data from forced vibration tests and ambient vibration monitoring. Recently, a low-intensity earthquake occurred in the region and the dam response was recorded by a seismic monitoring system. The previously calibrated numerical model was used to analyze the dynamic response of the dam under this seismic input, employing a dynamic boundary formulation that takes into account the wave propagation in the rock mass, preventing wave reflections. The results obtained show generally good agreement with the experimental measurements at the dam crest and abutments. The analysis methodology and the main issues involved in the modelling of arch dams under seismic action are discussed.